Art Merchandise As a Medium of Public Communication for Illustrator Martcellia Liunic Through The Art Label Liunic on Things - Zakiyah, Fifie Silmi; Jaeni, Jaeni (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2025)
Public communication in art means a process where artworks are not only enjoyed as aesthetic objects, but also to be interpreted and responded to by public audiences. In its development, technology has contributed to the expansion of the art medium to the realm that allows art to be conveyed closer to people's daily lives, one of which is through the concept of art merchandise. Through a case study of the art label Liunic on Things, this research aims to examine the creative strategy of art merchandise as a public communication of illustrator Martcellia Liunic to expand awareness of the identity of her work and image. The method used is case study qualitative research, through observation and literature study. The analysis in this research using Maurice Barrett's perspective theory approach The Nature of Art as a basic reference to observe how conception, operation and synthesis in the realization of art merchandise works by the art label Liunic on Things. The results show that Liunic on Things utilizes illustration art as the basis of its products creation, with bright and imaginative visual style characters applied to various daily products mediums, such as fashion, accessories, and decorations. This wearable art medium is not only a medium of aesthetic expression, but also a persuasive communication tool to build connections between artists and the public. In addition, art merchandise also functions as a medium for the extension of meanings and symbols that represent the artist's personal values, as well as a strategy to expand the accessibility of art to public spaces as well as creative economic opportunities. Through the analysis of visual elements on the surface of the product, it was found that the harmony of shape, color, and composition is the main key in presenting a consistent and communicative visual message.